Peranan Kinerja Amil Mengelola Zakat Produktif Dalam Mengentaskan Kemiskinan Di Kota Banda Aceh - Nurbismi Nurbismi; Zenitha Maulida; Ainul Ridha; Intan Novia Astuti (Jurnal Samudra Ekonomi dan Bisnis, 2019)
Aceh Province as an area with special authority that implementation of zakat distribution authority through non-structural institution Baitul Mal Based on Qanun 10/2007. The distribution of productive zakat targeted to be one of the achievement targets in reducing poverty in urban areas. Therefore, the distribution of productive zakat needs to be explored in a specific study in efforts to reduce poverty in Banda Aceh City. This research used multiple regression by placing the performance of amil zakat as a moderating variable. Sampling was conducted by 100 respondent of mustahik zakat productive in Banda Aceh. Based on the result, it is found that the amount of productive zakat, income, asset and business distribution are significantly influenced to decrease poverty level in Banda Aceh City. Performance amil not able to moderator variable for the field of business in zakat distribution. However, the performance of amil significantly effects as a moderating variable for productive zakat, income,and business assets in reducing the poverty of mustahik in Banda Aceh City. The moderation effects generated by the performance of amil are the pure moderator, the quasi moderator, and the predictor moderator. The conclusion that the performance of amil is able to reduce poverty levels in Kota Banda Aceh as a moderating variable.